Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-76929-3_2
|View full text |Cite
|
Sign up to set email alerts
|

A Static Birthmark of Binary Executables Based on API Call Structure

Abstract: Abstract.A software birthmark is a unique characteristic of a program that can be used as a software theft detection. In this paper we suggest and empirically evaluate a static birthmark of binary executables based on API call structure. The program properties employed in this birthmark are functions and standard API calls when the functions are executed. The API calls from a function includes the API calls explicitly found from the function and its descendants within limited depth in the call graph. To static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Choi et al suggested a static API birthmark for Windows [17]. Their static API birthmark is a set of possible API calls which is extracted statically by analyzing disassembled code.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…Choi et al suggested a static API birthmark for Windows [17]. Their static API birthmark is a set of possible API calls which is extracted statically by analyzing disassembled code.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…Software birthmarks can be classified into static and dynamic birthmarks [2][3][4][5][6][7][8][9][10][11][12][13]. Static birthmarks rely on syntactic structure of a program, and are extracted from it without its execution.…”
Section: A Software Birthmarks (Features Of Programs)mentioning
confidence: 99%
“…Software birthmark is an intrinsic feature of a program that can be used to identify the program and prove software plagiarism [2,3,4,5,7,9,10,11,12,13,15]. A birthmark can detect software theft by comparing the native characteristics of programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compilers that create byte code such as JAVA can extract relatively more accurate static birthmark compared to binary execution file, but it is difficult to extract by accurately analyzing code since accurate distinction between code and data is not possible with binary execution file. That's why dynamic birthmark method has been studied to extract birthmark in executed state of program [5], [6], [8], [9].…”
Section: Introductionmentioning
confidence: 99%